Altered rodent gait characteristics after 35 days in orbit aboard the International Space Station. (February 2020) - Kwok, Andy; Rosas, Samuel; Bateman, Ted A.; Livingston, Eric; Smith, Thomas L; Moore, Joseph; Zawieja, David C.; Hampton, Tom; Mao, Xiao W.; Delp, Michael D.; Willey, Jeffrey S.
Abstract: The long-term adaptations to microgravity and other spaceflight challenges within the confines of a spacecraft, and readaptations to weight-bearing upon reaching a destination, are unclear. While post-flight gait change in astronauts have been well documented and reflect multi-system deficits, no data from rodents have been collected. Thus, the purpose of this study was to evaluate gait changes in response to spaceflight. A prospective collection of gait data was collected on 3 groups of mice: those who spent 35 days in orbit (FLIGHT) aboard the International Space Station (ISS); a ground-based control with the same habitat conditions as ISS (Ground Control; GC); and a vivarium control with typical rodent housing conditions (VIV). Pre-flight and post-flight gait measurements were conducted utilizing an optimized and portable gait analysis system (DigiGait, Mouse Specifics, Inc). The total data acquisition time for gait patterns of FLIGHT and control mice was 1.5–5 min/mouse, allowing all 20 mice per group to be assessed in less than an hour. Patterns of longitudinal gait changes were observed in the hind limbs and the forelimbs of the FLIGHT mice after 35 days in orbit; few differences were observed in gait characteristics within the GC and VIV controls from the initial to the final gait assessment, and between groups. For FLIGHT mice, 12 out of 18 of the evaluated gait characteristics in the hind limbs were significantly changed, including: stride width variability; stride length and variance; stride, swing, and stance duration; paw angle and area at peak stance; and step angle, among others. Gait characteristics that decreased included stride frequency, and others. Moreover, numerous forelimb gait characteristics in the FLIGHT mice were changed at post-flight measures relative to pre-flight. This rapid DigiGait gait measurement tool and customized spaceflight protocol is useful for providing preliminary insight into how spaceflight could affect multiple systems in rodents in which deficits are reflected by altered gait characteristics.